1985
DOI: 10.3109/00048678509158810
|View full text |Cite
|
Sign up to set email alerts
|

Do Vietnam Veterans Suffer from Toxic Neurasthenia?

Abstract: This paper evaluates the claim that Vietnam veterans with psychiatric disorders are suffering from toxic neurasthenia--a neurasthenic syndrome caused by exposure to pesticides while serving in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Some veterans suffering from chronic somatic symptoms attributed their illness to the effects of herbicide exposure, while it was also claimed to have been the cause of birth defects in their children. Indeed, the Vietnam Veterans Association of Australia suggested that exposure to Agent Orange could have led to a form of 'toxic neurasthenia' (Hall & MacPhee 1985). To date, scientific and epidemiological studies have failed to identify a causal link (Boyle et al 1989;Anonymous 1994).…”
Section: Effects Of Agent Orangementioning
confidence: 99%
“…Some veterans suffering from chronic somatic symptoms attributed their illness to the effects of herbicide exposure, while it was also claimed to have been the cause of birth defects in their children. Indeed, the Vietnam Veterans Association of Australia suggested that exposure to Agent Orange could have led to a form of 'toxic neurasthenia' (Hall & MacPhee 1985). To date, scientific and epidemiological studies have failed to identify a causal link (Boyle et al 1989;Anonymous 1994).…”
Section: Effects Of Agent Orangementioning
confidence: 99%
“…The results suggest that the small excess of symptoms among Ranchhanders was due t o a combination of over-reporting (probably because of the publicity given to the adverse effects of exposure to the herbicides they sprayed) and to the difference in combat exposure between men who flew cargo aircraft well outside enemy range and the Ranchhanders who flew their aircraft at stalling speed at treetop level over enemy held positions. 29 Modest support for the Ranchhand study findings comes from the study by Suskind and Hertzberg26 of the health of 367 men, of whom 204 had been occupationally exposed to dioxin in the course of the manufacture of the herbicide 2,4,5-T. Exposure to dioxin contaminated herbicide was indicated by the occurrence of chloracne (a reliable sign of dioxin exposure) in 86 per cent of cases.…”
Section: Psychiatric Disordersmentioning
confidence: 95%
“…29 Modest support for the Ranchhand study findings comes from the study by Suskind and Hertzberg26 of the health of 367 men, of whom 204 had been occupationally exposed to dioxin in the course of the manufacture of the herbicide 2,4,5-T. Several features of the results, however, argue against their being interpreted as evidence in favour of the symptoms being a consequence of herbicide exposure.…”
Section: Psychiatric Disordersmentioning
confidence: 97%
See 2 more Smart Citations